LSD1 Activates PI3K/AKT Signaling Through Regulating p85 Expression in Prostate Cancer Cells - Wang, Zifeng; Gao, Shuai; Han, Dong; Han, Wanting; Li, Muqing; Cai, Changmeng (Frontiers in Oncology, 2019)
Lysine specific demethylase 1 (LSD1) functions as a transcriptional repressor through demethylating active histone marks such as mono- or di-methylated histone 3 lysine 4 (H3K4) and interacting with histone deacetylases. However, LSD1 can also act as an activator through demethylating repressive histone marks and possibly non-histone proteins. In prostate cancer (PCa) cells, LSD1 mediates the transcriptional activity of androgen receptor (AR), a ligand dependent nuclear transcription factor that drives PCa initiation and progression to the castration-resistant prostate cancer (CRPC). However, it is unclear whether LSD1 also regulates other growth promoting pathways independent of AR signaling in PCa cells. In this study, we show that LSD1 can activate PI3K/AKT pathways in absence of androgen stimulation, and we further demonstrate that LSD1 transcriptionally regulates the expression of PI3K regulatory subunit, p85, possibly through epigenetic reprogramming of enhancer landscape in PCa cells. Our study suggests that LSD1 has dual functions in promoting PCa development, that it enhances AR signaling through its coactivator function, and that it activates PI3K/AKT signaling through increasing p85 gene expression.